Staffing Data Management Through Information System at the Education Quality Assurance Institution of South Sulawesi Province - Meilyanti, Fifi; Niswaty, Risma; Jamaluddin, Jamaluddin (Pinisi Journal of Education and Management, 2022)
Staffing data management through the personnel management information system (SIMPEG) is all process activities carried out by SIMPEG operators in a WEB-based application that is designed as a solution to handle various matters in managing personnel data. Given the importance of managing employee data, improving the quality of personnel data management through the SIMPEG application is one of the priorities in the e-Government development stage. SIMPEG is very important in providing services to all existing personnel, because employees are an organizational asset that needs to be managed properly. Good employee management will improve employee performance in an agency. This study aims to determine the management of personnel data through the personnel management information system at the Education Quality Assurance Institute of South Sulawesi Province. This research uses qualitative method with descriptive research type. Informants in this study are; head of administration, SIMPEG operator, and 1 SIMPEG User. Data was collected using observation, interview and documentation techniques. The data analyzed is data collected at the time of the study. Activities in data analysis are data collection, data condensation, data presentation and data verification or conclusions. The results showed that the management of personnel data through the personnel management information system was in the good category. From the aspect of data collection, data management.